Recovery of Base Oil from Spent Automobile Oil Using Elementary and Binary Solvent Extraction - Abdulaziz, Yasser I.; Mahmood, Shaymaa M. A. (Nahrain University College of Engineering Journal, 2017)
This research was carried out to evaluate the effect of working parameters such as; type of solvent, solvent ratio, extraction temperature and mixing time on recovery of base oil from used oil by extraction / distillation technique. Bench scale experimental work was performed on spent motor oils collected from different service stations to select the suitable elementary solvents that could extract and regenerate the base oil such as (n- butanol, 2- propanol, and ethanol) and binary mixture of solvents such as (heptane and methyl ethyl ketone ) with (acetone). Different ratios of alcohol solvents to used lubricants from 1:1 to 4:1 (wt. /wt.) at atmospheric pressure with different extraction temperatures (30, 40, 50, 60oC) and different mixing time (15, 30, 45, 60min) were investigated. Moreover, three different types of earth fullers (acidic bentonite, basic bentonite and Dead Sea clay) were tested at different weight from 0.1 to 0.5g/20ml to bleach the base oil color which was regenerated at specific conditions of extracted temperature, solvent ratio and mixing time which were 40oC, 3:1 and 30min respectively.It has been found that the oil recovery and solvent recovery when using alcohol are progressively increased with increasing solvent/oil ratio to a certain limit. In such a manner that, n-butanol gives the highest extraction yield percentage of oil recovery and solvent recovery comparing with 2- propanol and ethanol. Moreover, higher mixing time granted higher percentage of base oil recovery and solvent recovery for 2- propanol and ethanol solvents. While insignificant effect of mixing time beyond 30min. on the recovery of oil and solvent was recorded with n- butanol.On the other hand, the oil recovery and solvent recovery are considerably increased with increasing binary solvent amount and with increasing the ratio of polar solvent (acetone) in the individual binary mixture. However, the binary solvent mixture of acetone plus methyl ethyl ketone is indicated to achieve highest extraction yield percentage of oil recovery. The final color of regenerated oil is evidently improved when it was treated with acidic bentonite and activated Dead Sea clay. On the other hand, there was no enhancement color recorded when it was treated with basic bentonite.